L-Histidina induz déficit estado dependente na evocação da memória em camundongos reexpostos ao labirinto em cruz elevado - Serafim, Kelly Regina (Universidade Federal de São Carlos, 2008)
The aim of the present study was to evaluate the effects of L-Histidine (a histaminergic precursor) on anxiety and memory retrieval in mice using the elevated plus maze (EPM). The test was performed on two consecutive days. On the first day (T1), the animals received an i.p injection of saline (SAL) or L-Histidine (LH), 40 minutes before the test at dose of 200mg/kg and 500mg/kg. The following experimental groups were formed: SALSAL (n=10-11); SAL-LH (n=10-10); LH-SAL (n=10-13) and LH-LH ( n=10-15). Testing begun by placing the subjects on the central platform of the maze facing an open arm and test sessions were 5 min in duration. A similar procedure was carried out for animals in the retest condition (T2) (i.e prior maze experience). During the test we analyzed behavioural parameters that comprised both conventional and ethological measures. All sessions were video-recorded by a camera positioned above and ~50 ° to the maze. Conventional measures were the frequencies of total, open (OAE) and closed arm entries, time spent in open (OAT) and closed (CAT) and central parts (CT) of the maze, and its respectively percentage %OAT, %CAT and %TC. Ethological measures comprised frequency scores for rearing; head-dipping (Dip) and stretched-attend postures (SAP). No significant differences were found, at the 200mg/kg dose, in open arm entries (Kruskall-Wallis; P= 0,1537) and open arm time (Kruskall-Wallis; P=0,824;), and at 500mg/kg dose no significant differences were observed in OAE and OAT [F(1,48)= 43,56; 13,01, p< 0,05, respectively) between the Sal-Sal and LH-LH groups in T1, indicating that L-histidine had no anxiolytic effect. At 200mg/kg dose a decreased of OA entries was observed for the SAL-SAL (Wilcoxon; P=0,017823), SAL-LH (Wilcoxon; P=0,00021) and LH-SAL (Wilcoxon; P=0,007) groups and in the OA time only for the SAL-SAL (Wilcoxon, P=0,0166) and SAL-LH (Wilcoxon; P=0,0284) groups. At the highest dose the LH-Sal group reduced open arm time and entries ([F(1,48)= 13.01 and 43.56; p<0.05) on the second trial, indicating that acquisition and storage was not affected by LH. Further, the LH-LH group did not reduce exploration time of the open arms during re-exposure, in both days indicanting an inability to evoke memory. No alteration in the locomotor activity represented by CAE was observed (p>0,05). Regarding a ethological behaviors, in both doses, the frequencies of Dipping was decreased (p<0,05) in the reexposure. In both treatment, the LH-LH group did not reduce the ratio of SAP during the retest, indicative of failure to evoke memory (p<0,05). Therefore, our results indicating that LH did not show anxiolitic effects but induces a state-dependent memory retrieval deficit in mice
Keywords: Medicina experimental - camundongo; Psicobiologia; L-Histidina; Evocação da memória; Labirinto em cruz elevado; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL